Universal scaling of robustness of ecosystem services to species loss - Samuel R. P.-J. Ross (Nature Portfolio, 2021)
Responses of ecosystem services to species losses are highly context-dependent. Here, the authors develop a model to identify general rules in the robustness of ecosystem service supply to species losses, and demonstrate its applicability using real-world ecosystem service networks.